2008
DOI: 10.1021/nl801417w
|View full text |Cite
|
Sign up to set email alerts
|

Pillared Graphene: A New 3-D Network Nanostructure for Enhanced Hydrogen Storage

Abstract: A multiscale theoretical approach was used to investigate hydrogen storage in a novel three-dimensional carbon nanostructure. This novel nanoporous material has by design tunable pore sizes and surface areas. Its interaction with hydrogen was studied thoroughly via ab initio and grand canonical Monte Carlo calculations. Our results show that, if this material is doped with lithium cations, it can store up to 41 g H 2 /L under ambient conditions, almost reaching the DOE volumetric requirement for mobile applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
523
3
18

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 738 publications
(556 citation statements)
references
References 49 publications
12
523
3
18
Order By: Relevance
“…This material is a two-dimensional (2D) allotrope of carbon comprising of a monoatomic sheet of sp 2 hybridized carbon atoms tightly bound in a honeycomb lattice that exhibits unique electronic structure, high specific surface area (2630 m 2 g -1 ), high electrical conductivity, chemical stability and structural flexibility [2][3][4]. These properties have generated a lot of curiosities for researchers to explore graphene and graphene based functional materials for a wide range of possible applications such as electronics, sensors, composite materials, photocatalysis, energy storage and conversion [5][6][7][8][9][10]. Supercapacitors are energy storage systems that have attracted interest because of their unique mechanism of storing energy by accumulating charges at the electrode-electrolyte interface [11].…”
Section: Introductionmentioning
confidence: 99%
“…This material is a two-dimensional (2D) allotrope of carbon comprising of a monoatomic sheet of sp 2 hybridized carbon atoms tightly bound in a honeycomb lattice that exhibits unique electronic structure, high specific surface area (2630 m 2 g -1 ), high electrical conductivity, chemical stability and structural flexibility [2][3][4]. These properties have generated a lot of curiosities for researchers to explore graphene and graphene based functional materials for a wide range of possible applications such as electronics, sensors, composite materials, photocatalysis, energy storage and conversion [5][6][7][8][9][10]. Supercapacitors are energy storage systems that have attracted interest because of their unique mechanism of storing energy by accumulating charges at the electrode-electrolyte interface [11].…”
Section: Introductionmentioning
confidence: 99%
“…The combination of nanotube carpets and graphene is an approach to extend those properties into three dimensions [12][13][14] . However, high-quality, single-and few-walled carbon nanotube (CNT) carpets with large SSA are usually grown on alumina, an insulator that immobilizes the catalyst particles and supports efficient growth 15,16 .…”
mentioning
confidence: 99%
“…The group of Froudakis has shown that instead of pillaring graphene sheets with organic molecules, a 3D network nanostructure of graphene and carbon nanotubes could be used for hydrogen storage. 173,174 They showed that by doping the framework with Li + cations, the structure can potentially achieve a hydrogen capacity of more than 10 wt% at 77 K and 100 bar, satisfying the requirement of DOE for mobile applications. 174 Recently, a 3D pillared structure of GO and carbon nanotubes has been experimentally fabricated by utilizing the liquid crystalline properties of GO in aqueous media to construct the ordered architecture.…”
Section: Gas Adsorptionmentioning
confidence: 99%